Physical and Chemical Modification of Okara Flour and Its Effect on Chicken Nugget - Isyqi Aulia Rohmah; Iffah Muflihati; Rizky Muliani Dwi Ujianti; Arief Rakhman Affandi (Indonesian Association of Food Technologists, 2026)
Okara is a by-product of soybean processing that remains underutilized. Okara flour requires physical and chemical modifications to improve its characteristics before it can be used in chicken nuggets. This study aims to determine the effect of physical and chemical modifications on the functional properties of okara flour and to determine the type and percentage of okara flour substitution on the characteristics of chicken nuggets. This research used okara flour treated with various modifications (autoclaving, cooling, acid hydrolysis, and a combination of acid hydrolysis and autoclaving-cooling) and applied it to a chicken nugget formulation at 5% and 10% flour substitution levels. Flour analysis results showed that autoclaving-cooling modification tended to improve emulsion stability and oil absorption. Acid hydrolysis modification and combination tended to increase flour emulsion stability but decreased oil absorption. The results of chicken nugget analysis showed that physical and chemical modification affected the proximate nutritional value. The type of flour modification tends to increase the emulsion stability of chicken nuggets but reduces water absorption. The best method, according to this study, is chicken nuggets, using a combination of methods, such as okara flour.